A Model for Effectiveness of E-learning at University - Marzieh Aali; Fatemeh Narenji Thani; Mohammad Reza Keramati; Armin Garavand (Journal of Information Technology Management)
In the digital age, e-learning systems have been employed as new equipment in the higher education system in different universities. Consideringthe importance of optimization of this system, this research is aimed at providing a modelfor the effectiveness of e-learning at in higher education systems. The study is a descriptive survey study in terms of its data collection method.The population includes all the students of electronic courses at the University of Tehran. This population includes 1481 students of the University of Tehran in the academic year 2019-2020. Regarding the population size, 300 students were selectedbased onstratified sampling, using Cochran’s formula.Lisrel and Amos softwarewere used for data analysis. In the first step, byliterature review, and based on the collected information, 87 components were identified to be related toe-learning effectiveness. Then, based on the highest frequency of the identified components in one hand, and their significance from the experts’ viewpoints, on the other hand, 14 components were finally selected and classified in three major classes including;pedagogical, individual and technicalrelated factors.